Cash plus: exploring the mechanisms through which a cash transfer plus financial education programme in Tanzania reduced HIV risk for adolescent girls and young women. (22nd July 2019) - Pettifor, Audrey; Wamoyi, Joyce; Balvanz, Peter; Gichane, Margaret W; Maman, Suzanne
Abstract: Introduction: Cash transfers have been promoted as a means to reduce HIV risk for adolescent girls and young women (AGYW) in sub‐Saharan Africa. One of the main mechanisms whereby they are hypothesized to reduce risk is by deterring transactional sex. In this paper, we use qualitative methods to explore participant experiences, perspectives and reported behaviours of a cash transfer plus financial education programme among out of school, 15‐ to 23‐year‐old AGYWs in rural Tanzania with a focus on partner choice and transactional sex. Methods: We conducted 60 in‐depth interviews (IDIs) and 20 narrative timeline interviews with participants of the PEPFAR DREAMS Sauti/WORTH+ cash transfer programme between June 2017 and July 2018. Interviews were taped, transcribed and translated from Kiswahili to English. Transcripts were coded and analysed for key themes. Results: We found that participants in a cash transfer plus programme discussed behaviours that could reduce HIV risk through decreasing their dependence on male sex partners. There appeared to be two main mechanisms for this. One, young women discussed the cash transfer providing for basic needs (e.g. food, toiletries) which appeared to reduce their dependence on male sex partners who previously provided these goods (e.g. transactional sex). This experience was more pronounced among the poorest participants. Two, young women discussed how the financial education/business development aspect of the programme empowered them to refuse some sex partners; unmarried women discussed these experiences more than married women. Social support from family and programme mentors appeared to strengthen young women's ability to successful start businesses, produce income and thus be less dependent on partners. Conclusions: The cash transfer programme may have reduced AGYW engagement in transactional sex that occurred to meet basic needs (one form of transactional sex). The financial education/business development and mentorship elements of the programme appeared important in building AGYW agency, self‐esteem and future orientation which may support AGYWs in refusing unwanted sex partners. Future cash plus programmes should consider adding or strengthening financial education and job skills training, mentorship and future orientation to see stronger and perhaps sustainable outcomes for HIV prevention.